COMPLICATED GRIEF AND RELATED BEREAVEMENT ISSUES FOR DSM-5 - Shear, M. Katherine (2011)
Bereavement is a severe stressor that typically incites painful and debilitating symptoms of acute grief that commonly progresses to restoration of a satisfactory, if changed, life. Normally grief does not need clinical intervention. However, sometimes acute grief can gain a foothold and become a chronic debilitating condition called complicated grief. Moreover, the stress caused by bereavement, like other stressors, can increase the likelihood of onset or worsening of other physical or mental disorders. Hence some bereaved people need to be diagnosed and treated. A clinician evaluating a bereaved person is at risk for both over-and under-diagnosis, either pathologizing a normal condition or neglecting to treat an impairing disorder. The authors of DSM IV focused primarily on the problem of over-diagnosis, and omitted complicated grief because of insufficient evidence. We revisit bereavement considerations in light of new research findings. This paper focuses primarily on a discussion of possible inclusion of a new diagnosis and dimensional assessment of complicated grief. We also discuss modifications in the bereavement V code and refinement of bereavement exclusions in major depression and other disorders.